2023
DOI: 10.1101/2023.02.26.530153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiscale networks in multiple sclerosis

Abstract: Complex diseases such as Multiple Sclerosis (MS) cover a wide range of biological scales, from genes and proteins to cells and tissues, up to the full organism. We conducted a multilayer network analysis and deep phenotyping with multi-omics data (genomics, phosphoproteomics and cytomics), brain and retinal imaging, and clinical data, obtained from a multicenter prospective cohort of 328 patients and 90 healthy controls. Multilayer networks were constructed using mutual information, and Boolean simulations ide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…One promising treatment-sensitive biomarker for disease activity in pwMS currently being studied is the assessment of high-frequency serum neurofilament light chain levels (130). ML and AI techniques are also increasingly employed in the quest for new MS biomarkers [see, e.g., (131)]. One more reason, to finally leave the traditional pathway and to go digital in MS care.…”
Section: Walking Along the Pathway: Ms Treatment Could Change For The...mentioning
confidence: 99%
“…One promising treatment-sensitive biomarker for disease activity in pwMS currently being studied is the assessment of high-frequency serum neurofilament light chain levels (130). ML and AI techniques are also increasingly employed in the quest for new MS biomarkers [see, e.g., (131)]. One more reason, to finally leave the traditional pathway and to go digital in MS care.…”
Section: Walking Along the Pathway: Ms Treatment Could Change For The...mentioning
confidence: 99%
“…We noted proteins such as NTRK1 (neurotrophic receptor tyrosine kinase 1), APP (Amyloid-beta precursor protein), MAPK1, and MAP2K1. These proteins play pivotal roles in signal transduction pathways and glial cell differentiation (24)(25)(26)(27)(28)(29) . Despite variability in the expression profiles across species, the data suggested that PDRN might exert distinct influences on the MAP kinase pathway, thereby affecting ADORA2A interactions and neuronal cell differentiation (Fig.…”
Section: Network Of Differentially Expressed Adora2a Interactome Asso...mentioning
confidence: 99%
“… 286 We propose using clinical phenotype clusters (e.g., AIS B-severe neuropathic pain-prominent dysautonomia) to serve as anchors for molecular network assessments, critical transition events, and the generation of Physiome models. We suggest an initial approach to SCI systems-medicine via multi-variate modeling casting a wide variable net across different scales, 287 including demographics factors (age/sex), AIS, MRI injury severity, multi-organ injury, serum biomarkers, genetic characterization (GWAS) to identify relevant SNPs, peripheral blood inflammatory response and immune depression markers, autonomic instability and blood pressure, complications, and microbiome changes. 288 Serial measures are important to understand how phenotypes such as neuropathic pain and metabolic syndrome evolve, the impact of allostatic stress, and to assess epigenetic markers, including aging.…”
Section: Modeling Of Sci As a Multi-system Diseasementioning
confidence: 99%